DEVELOPMENT AND EVALUATION OF A FRAMEWORK FOR CREATING WEB-BASED LEARNING MODULES: A PEDAGOGICAL AND SYSTEMS PERSPECTIVE - Janicki, Thomas; Liegle, Jens O. (Online Learning, 2001)
Educational content on the Internet is rapidly increasing. Educational institutions and businesses are placing more course material online to supplement classroom and business training situations. Prior researchers have reported that this new web-based training technology (which has its foundation in computer-based training) has not integrated sound pedagogical practices into the authoring process when developing new tutorials. This research merges theories from the instructional design and web-based design researchers in a framework for more effective web-based tutorials. To test the effectiveness of this model, a prototype computer system is developed. This system named WeBTAS (Web-Based Tutoring Authoring System) is reviewed by two different panels of educators. These panels report that the prototype system does promote five different learning principles as part of the authoring process. In addition the system was implemented on a pilot test basis and its initial observations are that it produces an average of 15% more learning content in the same development time as conventional authoring tools.